Single phase matrix converter for boost inverter operation controlled using Xilinx FPGA / Mohd Hafiz Mohd Nasir - Mohd Nasir, Mohd Hafiz (2011)
This thesis is concerned on Field Programmable Gate Array (FPGA) design for control implementations of the Single Phase Matrix Converter (SPMC) operating as a Boost Inverter. The main attribute of the boost inverter topology is the fact that it generates an ac output voltage larger than the dc input voltage depending on the instantaneous duty cycle. The Single Phase Matrix Converter (SPMC) power circuit uses the Insulated Gate Bipolar Transistor (IGBTs) as power switching devices. The Sinusoidal Pulse Width Modulation (SPWM) technique is used to synthesize the output voltage. XILINX Field Programmable Gate Array (FPGA) was used as a digital controller of the converter. The selected simulation results are presented to verify the proposed operation of boost inverter.